An unexpected deterrent in diagnosing refractory celiac disease and enteropathy-associated T-cell lymphoma: a gluten-free diet - Nooreen Hussain; Faiz Hussain; Tulika Chatterjee; Jan N. Upalakalin; Teresa Lynch (Greater Baltimore Medical Center, 2018)
Enteropathy-associated T-cell lymphoma (EATL) is a rare disease found in the small bowel and is seen most commonly in patients with refractory celiac disease (RCD). We present a case of an elderly male with celiac disease (CD) diagnosed in childhood with months of abdominal pain and diarrhea despite attempting to avoid gluten in his diet. After persistent symptoms for months, the patient was admitted for an acute abdomen and was found to have small bowel perforation due to a jejunal mass that was diagnosed as an EATL. In 2-5% of adult onset CD, serious complications such as RCD or malignancy develop. The clinical course for EATL is aggressive and generally has a poor prognosis. This case highlights the importance of early clinical suspicion for a small bowel malignancy in patients with a long-standing history of CD and acute worsening of symptoms. Early workup and diagnosis is vital in improving morbidity and mortality in patients with EATL.